Evaluation Impact of the European Union Anti-Deforestation Regulation (EUDR) Policy: Empirical Study of Indonesian Agricultural Product Exports - Indrasto, Haryo Bimo Budi; Asyifa, Hanif Nindy; Kuncoro, Trian Gigih (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to analyze the impact of the European Union Anti-Deforestation Regulation (EUDR) on the export performance of Indonesia's agricultural products. Specifically, it evaluates how the EUDR affects export volumes to European Union (EU) member countries compared to non-EU countries. Additionally, the study examines the role of macroeconomic variables such as Gross Domestic Product (GDP), population size, exchange rates, and economic distance in shaping Indonesia’s international trade patterns. Methodology: This research employs a quantitative approach using the gravity trade model as the analytical framework. Panel data from 20 of Indonesia’s trading partners, including both EU and non-EU countries, for the period 2018–2023 were used. The Poisson Pseudo Maximum Likelihood (PPML) estimation method was applied to address issues of heteroskedasticity and zero trade values in bilateral trade data. Key variables analyzed include GDP, population size, exchange rates, economic distance, as well as dummy variables for the implementation of EUDR and trading partner status (EU vs. non-EU). Results: The findings indicate that the implementation of EUDR has a significant negative effect on the export volume of Indonesia's agricultural products to EU member countries. Conversely, the EUDR's impact on exports to non-EU countries is statistically insignificant. The analysis also reveals that GDP growth in trading partner countries positively influences export volumes, while the depreciation of the Indonesian Rupiah against the US Dollar significantly reduces export performance, particularly in sectors dependent on imported raw materials. Economic distance between countries has a minimal impact, largely due to international trade agreements that reduce trade barriers. Applications/Originality/Value : This study provides valuable insights into the impact of international environmental regulations on the export performance of developing countries. By integrating the gravity trade model with the PPML approach, the research offers an innovative method for assessing the effects of EUDR in the context of global trade. The findings are relevant for policymakers in designing strategies to adapt to global environmental regulations, such as strengthening trade relations with non-EU countries and promoting sustainable practices in the agricultural sector. The originality of this study lies in its use of multi-country panel data and its focus on the interplay of economic, policy, and environmental variables in shaping trade patterns.